Ecology and phenology of the bat tick Argas (Carios) dewae (Acari: Argasidae) - Lisa Godinho; Emile van Lieshout; Stephen Griffiths; Mackenzie L. Kwak; Ala Tabor (Parasitology)
Although 12 soft tick species (Argasidae) are native to Australia, the ecology of most is poorly known. Argas dewae parasitizes several insectivorous bat species and has been recorded on humans. Therefore, understanding its ecology is crucial for wildlife health management and public health preparedness. To address this knowledge gap, A. dewae populations were monitored from 2 bat hosts (Chalinolobus gouldii and Austronomus australis) using bat boxes at 3 sites in Victoria, Australia, for 28 months (July 2005–December 2007). A phenological profile undertaken for A. dewae revealed that tick load on bat hosts increased throughout winter and peaked in the first month of spring, before collapsing and remaining low throughout the drier late spring and summer periods. There was also further investigation of the relationship between 2 response variables (tick infestation risk and tick load) and a range of explanatory variables (body condition index, sex, age class, bioseason, site, bat density per nest box). In C. gouldii, site was the only significant predictor of A. dewae infestation risk, while load was correlated with several variables including age class, sex, bioseason, roost density and body condition index. This paper also reports the first records of A. dewae from 6 bat species in 3 bat families (Miniopteridae: Miniopterus australis; Molossidae: A. australis; Vespertilionidae: Chalinolobus morio, Myotis Macropus, Vespadelus darlingtonia, Vespadelus regulus) and a second record of A. dewae from a human. The first distribution records are presented for A. dewae in South Australia, the Australian Capital Territory and Queensland.